2010
DOI: 10.1159/000314970
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Adrenal Steroids and Their Precursors as a Measure of Maturity of Adrenocortical Function in Very Premature Newborns

Abstract: Background: Relative adrenocortical insufficiency is often seen in sick premature newborns. As the human fetal adrenal cortex does not express the 3β-hydroxysteroid dehydrogenase (3β-HSD) enzyme before about 23 weeks of gestation, we hypothesized that this enzymatic step may be rate limiting in cortisol synthesis in premature infants of less than 28 weeks postmenstrual age at birth. Methods: We measured cord, first day (D0) and median fourth day (D4) serum 17-OH-pregnenolone (17-OHPreg), 17-OH-progesterone (17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The surge in cortisol production is absent in preterm infants during clinical illness36). Although the human fetal adrenal cortex does not express the 3βHSD enzyme prior to 23-week gestation, there is no evidence of significant immaturity in adrenal 3βHSD activity in preterm infants born between 24-28 weeks of gestation37). Blood concentrations of cortisol and other steroid hormones are no lower in preterm infants with late onset adrenal insufficiency than in control preterm infants38).…”
Section: Adrenal Gland Of Preterm Infantsmentioning
confidence: 99%
“…The surge in cortisol production is absent in preterm infants during clinical illness36). Although the human fetal adrenal cortex does not express the 3βHSD enzyme prior to 23-week gestation, there is no evidence of significant immaturity in adrenal 3βHSD activity in preterm infants born between 24-28 weeks of gestation37). Blood concentrations of cortisol and other steroid hormones are no lower in preterm infants with late onset adrenal insufficiency than in control preterm infants38).…”
Section: Adrenal Gland Of Preterm Infantsmentioning
confidence: 99%
“…This is thought to be secondary to the absence of 3-b-hydroxysteroid dehydrogenase enzyme activity until approximately 23 weeks' gestation in combination with suppression of the fetal hypothalamic-pituitary-adrenal (HPA) axis by maternal cortisol. However, Nykanen et al (5) found that there was no evidence of immaturity in 3-b-hydroxysteroid dehydrogenase activity in preterm infants delivered between 24 and 28 weeks of gestation.…”
Section: Adrenal Functionmentioning
confidence: 98%
“…Although the human fetal adrenal cortex does not express the 3βHSD enzyme before approximately 23 weeks gestation, pre vious studies have shown no evidence of significant immaturity in adrenal 3βHSD activity in preterm infants between 2428 weeks gestation 19,20) . In contrast, decreased activity of 11βhy droxylase, which converts 11deoxycortisol to cortisol, is pro minent.…”
Section: Adrenocortical Function Of Preterm Infantsmentioning
confidence: 99%
“…In contrast, decreased activity of 11βhy droxylase, which converts 11deoxycortisol to cortisol, is pro minent. Reduced activity of 11βhydroxylase, rather than that of 3βHSD, is thought to explain the inappropriate production of cortisol in the preterm adrenal gland 19,20) (Figure 1).…”
Section: Adrenocortical Function Of Preterm Infantsmentioning
confidence: 99%